Complex requirements analysis for the high-level design of embedded systems - Parkhomenko, А.; Gladkova, О. (Видавництво Львівської політехніки, 2014)
In the paper the requirements analysis that must be considered at designing embedded systems was performed. Describes peculiarities of the structuring requirements and developed a model of requirements to the created embedded system. Methodology of creating requirements, taking into account the processes of their definition and analysis was proposed. The results of application of the developed requirements model during project implementation the embedded system to control of mobile platform were presented. У роботі виконано аналіз вимог, які необхідно враховувати під час проектування вбудованих систем. Описані особливості структурування вимог та розроблена модель вимог для вбудованих систем. Запропоновано методику створення вимог з урахуванням процесів їх визначення та аналізу. Наведено результати практичного застосування розробленої моделі вимог при реалізації проекту вбудованої системи управління рухомою платформою.
Комплексний аналіз вимог при високорівневому проектуванні вбудованих систем
Keywords: embedded system; requirements classification; requirements analysis; requirements model; methodology of creating requirements; regulatory documentation; mobile platform; вбудована система; класифікація вимог; аналіз вимог; модель вимог; методика створення вимог; нормативна документація; рухома платформа